AN ANALYSIS OF EFL STUDENTS' PRONUNCIATION ACCURACY AT THE ENGLISH EDUCATION DEPARTMENT OF UIN SUSKA RIAU - Wapuja Jayati Gathy NST; Idham Syahputra (State Islamic University of Sultan Syarif Kasim Riau, 2026)
Pronunciation accuracy is an essential component of oral communication because it directly influences intelligibility and comprehensibility. Despite studying English for several semesters, many English as a Foreign Language (EFL) students continue to experience difficulties in producing English sounds accurately. This study aimed to analyze the pronunciation accuracy of fourth-semester students at the English Education Department of UIN SUSKA Riau. The research employed a descriptive quantitative design involving fifteen students selected through purposive sampling. The data were collected through a pronunciation test covering four pronunciation aspects: consonant, vowel, word stress, and intonation. Students' performances were evaluated independently by two raters using an analytic pronunciation scoring rubric, and the average scores were analyzed using descriptive statistics in IBM SPSS Statistics. The findings revealed that the overall mean score of students' pronunciation accuracy was 13.60 (SD = 1.0212), indicating a moderate level of pronunciation accuracy. Among the four aspects, consonant accuracy obtained the highest mean score (3.87), followed by intonation (3.67), vowel accuracy (3.30), and word stress (3.07). The findings indicate that students generally performed better in segmental features than supra segmental features, particularly word stress. Therefore, greater emphasis on pronunciation instruction, especially in supra segmental aspects, is recommended to improve students' pronunciation proficiency.